Refractory cardiogenic shock caused by zinc phosphide toxicity. Issue 2 (4th March 2023) - Mittal, Nitish; Elmassry, Mohamed; Abohelwa, Mostafa
Abstract: Zinc phosphide toxicity is a rare entity that presents most frequently among farmers in developing countries who use it as a rodenticide. The phosphine gas released after the ingestion inhibits cytochrome c oxidase, disrupting the mitochondrial physiology and oxidative phosphorylation and causing myocardial stunning. Here we present a case of a 20-year-old man who attempted suicide with zinc phosphide toxicity. Initially, he was hemodynamically stable with a normal ejection fraction; however, in a few hours, he deteriorated quickly and became hemodynamically unstable, with rapid deterioration of his ejection fraction to 20%. He was started on norepinephrine and then dobutamine; however, he had cardiac arrest from refractory cardiogenic shock despite resuscitative measures.